MAQASID DAKWAH: TRENDS AND RESEARCH DEVELOPMENTS - Ismail, Ahmad Syihan; Hamid, Siti Nur Hazirah; Abdullah, Yusuf Marlon (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
The concept of Maqasid Dakwah, which integrates the higher objectives of Islamic preaching with contemporary societal needs, has increasingly become a focal point in Islamic scholarship. Despite this growing interest, a comprehensive understanding of its research trends, thematic development, and global scholarly contributions remains limited. This study aims to analyze the evolution and direction of Maqasid Dakwah research using bibliometric techniques to uncover publication patterns, dominant themes, and collaboration networks over the past two decades. The data collection was conducted through an advanced title-based search in the Scopus database using three key terms: maqasid, policy, and dakwah. The search was limited to English-language journal articles published between 2005 and 2024. After applying inclusion and exclusion criteria, a total of 670 documents were identified as relevant. Data cleaning and standardization were carried out using OpenRefine, while Scopus Analyzer and VOSviewer software were employed to conduct performance analysis, keyword co-occurrence mapping, and co-authorship visualization. The results indicate a sharp increase in publication output between 2004 and 2024, with Malaysia and Indonesia leading in terms of research productivity. Subject areas were dominated by social sciences, arts and humanities, Islamic studies, and economics, reflecting the multidisciplinary nature of Maqasid Dakwah. Frequently occurring keywords such as maqasid al-shariah, Islamic law, Islamic education, and sustainable development goals point to an evolving focus on ethical frameworks, policy relevance, and community well-being. The analysis also revealed limited global collaboration and underrepresentation in digital platforms and applied sciences. In conclusion, this study highlights the expanding role of Maqasid Dakwah in academic discourse and emphasizes the need for greater international cooperation and thematic diversification to strengthen its impact across disciplines and regions.